HORIZONTAL AXIS MARINE CURRENT TURBINE DESIGN FOR WIND-ELECTRIC HYBRID SAILING BOAT - Ekinci, Serkan; Alvar, Mustafa (BRODARSKI INST, 2017)
In recent decades, the number of theoretical studies and applications on electric power production from renewable sources such as wind, solar, sea and tidal flows, has been increasing rapidly. Marine Current Turbines (MCTs), among the power turbines, produce power from alternating flows and are a means of power production even at lower flow rates in oceans and seas. In this study, while maintaining functional requirements, an initial and detailed design (mechanic and hydrodynamic), of an MCT fixed on a sailing boat and at sail which extracts power from the flow around the boat, is undertaken. In the design stages, for analysis and optimization of the marine turbine blade design, the Momentum Blade Element Method is utilized. The Horizontal Axis Marine Turbine (HAMT), determined by the initial and mechanical design, is illustrated with its components included. Computational fluid dynamics (CFD) analyses, covering turbine pod geometry at required flow rates and turbine speeds are performed. These analyses are performed very close to real conditions, considering sailing with and without the turbine running (on and off states). The alternator is determined from the results, and the final design which meets the design requirements, is obtained. As a result, a user friendly and innovative turbine design for sail boats, offering more power and efficiency, which is longer lasting compared to solar and wind technologies, that also makes use of renewable sources, such as wind and/or solar, and in addition stores and uses accumulated energy when needed, is proposed.
Keywords: Renewable energy; marine current turbine; momentum blade element method; computational fluid dynamics; TIDAL TURBINES; PERFORMANCE; Engineering